Incidence, clinical features, and outcomes of posterior circulation ischemic stroke: insights from a large multiethnic stroke database - Imam, Yahia Z.; Chandra, Prem; Singh, Rajvir; Hakeem, Ishrat; Al Sirhan, Sally; Kotob, Mona; Akhtar, Naveed; Kamran, Saadat; Al Jerdi, Salman; Muhammad, Ahmad; Haroon, Khawaja Hasan; Hussain, Suhail; et al. (Frontiers in Neurology, 2024)
Background: Posterior cerebral circulation ischemic stroke (PCS) comprises up to 25% of all strokes. It is characterized by variable presentation leading to misdiagnosis and morbidity and mortality. We aim to describe PCS in large multiethnic cohorts.A retrospective review of a large national stroke data base from its inception on the 1st of January 2014 till 31 December 2020. Incidence per 100,000 adult population /year, demographics, clinical features, stroke location and outcomes were retrieved. We divided the cohort into patients from MENA (Middle East and North Africa) and others.Results: 1,571 patients were identified. The incidence of PCS was observed to be rising and ranged from 6.3 to 13.2/100,000 adult population over the study period. Males were 82.4%. The mean age was 54.9+12.7 years (median 54 years, IQR 46, 63). MENA patients comprised 616 (39.2%) while others were 954 (60.7%); of these the majority (80.5%) were from South Asia.Vascular risk factors were prevalent with 1,230 (78.3%) having hypertension, 970 (61.7%), diabetes, and 872 (55.5%) having dyslipidemia. Weakness 944 (58.8%), dizziness 801 (50.5%), slurred speech 584 (36.2%), were the most common presenting symptoms. The mean National Institute of health Stroke Score (NIHSS) score was 3.8+4.6 (median 3, IQR 1, 5). The overall most frequent stroke location was the distal location 568 (36.2%). The non-MENA cohort was younger, less vascular burdened and more frequent proximal stroke location (p<0.05).Dependency or death at discharged were seen in 39.5% and associated with increasing age, proximal and multilocation involvement; while at 90 days it was 27.4% and was associated with age, male sex, and having a MENA nationality (p<0.05).